Production Offshoring and the Skill Composition of Italian Manufacturing Firms: A Counterfactual Analysis - Roberto Antonietti; Davide Antonioli (Fondazione Eni Enrico Mattei (FEEM), 2007)
This work explores the effects of cross-border relocation of production on the skill composition of Italian manufacturing firms. Its aim is to assess if the firms strategy to offshore production activities towards cheap labor countries determines a bias in the relative employment of skilled versus unskilled workers. Using a balanced panel of firm-based data across the period 1995-2003, we test this skill-bias hypothesis by means of a counterfactual experiment in which we employ a difference-in-differences propensity score matching estimator in order to control for selectivity bias without relying on a specific functional form of the relations of interest. In line with the literature, our results point to confirm a general, although weak, skill bias effect of production offshoring on the labor-force composition of Italian manufacturing: in particular, we find that firms farming out production stages in 1998-2000 show an upward shift in the skill ratio with respect to the counterfactual of firms not moving their production abroad. However, when we look at the single components of the skill ratio, we find that the skill bias effect is primarily driven by a fall in the employment of production workers, while a weak or not significant effect is found with respect to the employment of skilled personnel.
Keywords: J24; F16; L24; 330; Production Offshoring; Skill Bias; Difference-in-Differences; Propensity; Auslandsverlagerung; Auslandsverlagerung; Internationale Produktion; Qualifikation; Verarbeitendes Gewerbe; Italien